Penerapan Hukum Newton dalam Menghitung Sudut Efektif pada Gerakan Bench Press - Safitri, Niken Ari; Natalisanto, Adrianus Inu; Munir, Rahmawati (Program Studi Fisika, Jurusan Fisika, FMIPA, Universitas Mulawarman, 2023)
Bench press is a form of powerlifting exercise that aims to increase the strength and endurance of the muscles of the upper body, that is, the muscles of the chest, arms, and shoulders. The characteristic of the bench press exercise is to lift or push the weight using both hands in a supine position. The purpose of this research is to determine the effective angle required for lifting weights with the least amount of thrust (biomechanics aspects). The research steps were carried out in four stages, namely: first, designing biomechanics mathematical equations; second, experiments on people doing bench press movements; third, processing biomechanics data; and fourth, analysis and discussion of biomechanics data. According to the study's findings, an effective angle was obtained by analyzing the thrust to lift the barbell, that is, the angle flanked by the upper and lower arms, which is approximately 89°-114° for those who use the smallest thrusts on the grip: 0.4 m, 0.5 m, and 0.6 m. It can be concluded that the wider the distance between the grips, the greater the thrust required.